A Comparative Impact Assessment of Hail Damage to Tile and Built-Up Roofing Systems: A Comprehensive Review - Gayatri Thakre; Vinayak Kaushal; Mohammad Najafi (CivilEng)
Hail causes damage to property, including roofs, automobiles, and crops, with an average annual loss of USD 850 million. In residential structures in the southern U.S., tile roofing systems are common due to their resistance to the impact of hail and their long service life. Commercial low-slope roof systems are equally prone to hail-strike damages as steep residential roof systems. The objective of this paper is to present a literature review, inspection protocol, and case studies on a comparative assessment of the hail threshold for built-up roof (BUR) and tile roof (TR) systems. More than 90 published papers determining the hail impact assessment of different roofing systems from 1969 through 2024 were studied and analyzed. This study develops a comparative hail damage assessment study between BUR and TR systems and provides detailed statistical data and hail thresholds for various built-up roof composition systems. In addition, the different failure modes and their causes, the characteristics of hail impacts, and the variables influencing the impact resistance of these roofing systems were examined using field studies. To better understand the effects, it is recommended that an intelligent model be developed to predict the hail resistance threshold of various configurations of BUR and TR systems with critical variables.